Measuring microenvironments for global change: DIY environmental microcontroller units (EMUs). Issue 4 (30th December 2018) - Mickley, James G.; Moore, Timothy E.; Schlichting, Carl D.; DeRobertis, Amber; Pfisterer, Emilia N.; Bagchi, Robert
Abstract: Rapid climate change is generating an urgent need to understand how organisms respond to environmental variation. Understanding these responses at an organismal level requires environmental data at finer spatial and temporal scales than is available from global datasets. Current measurement technologies force a trade‐off between collecting data at the broad spatial scales relevant to global change while simultaneously capturing environmental variation at the fine spatial and temporal scales relevant to organisms. The greatest hurdle to ameliorating this trade‐off is the cost of commercially available sensors. Here, we introduce environmental microcontroller units (EMUs), data loggers designed and built to accurately measure fine‐scale variation in temperature, humidity, light, and soil moisture at low cost. We detail how to construct EMUs, test their utility in measuring microenvironment under field settings, and compare their accuracy to commercial data loggers in the same field setting. Parts for EMUs cost less than $20 per unit; an order of magnitude less than comparable commercial loggers. Their cost‐effectiveness allows for many more units to be deployed to measure microenvironment, providing the capacity for broader spatial sampling. Their programmability and modularity make them flexible, and they can be quickly assembled using unskilled labour. Using EMUs in a field setting, we detected microenvironmental variation in temperature, humidity, irradiance, and soil moisture at scales of <80 m. Despite their affordability, EMUs were of comparable accuracy to that of commercial sensors. With the growing availability of inexpensive microcontrollers and hobbyist electronics, the time is ripe to tap into the versatility and computational power of do‐it‐yourself electronics to address critical ecological questions. In addition to marked cost advantages, EMUs are both more flexible and more capable than most commercial options, providing the tools to bypass the trade‐off between the extent and resolution of environmental measurement. Yet, their simple design makes constructing them feasible for ecologists without specialist backgrounds in electronics.